2022
DOI: 10.1007/s12298-022-01134-2
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the importance of ionic and osmotic components of salt stress on the photosynthetic efficiency of epiphytic lichens

Abstract: Salt stress can significantly disrupt the functioning of lichens which are self-sufficient symbiotic organisms inhabiting various severe environments. The aim was to test the effect of salt and sucrose on the photosynthetic efficiency of two selected epiphytic lichens inhabiting the interior of the land. Firstly, we compared the effect of salt and sucrose solutions of different concentrations. Secondly, the effect of salt and sucrose solutions with identical osmotic pressures was compared. The results showed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 57 publications
1
4
0
Order By: Relevance
“…Prolonged drying and dehydration cause greater damage to the structure and functional recovery of PSII than short-term desiccation. This is in line with some previous studies that showed that only a prolonged stay in the desiccated state caused significant degradation of chlorophyll [41,42]. The desiccation tolerance is species-specific and depends on the speed, intensity and duration of water loss during dehydration [6].…”
Section: Discussionsupporting
confidence: 92%
“…Prolonged drying and dehydration cause greater damage to the structure and functional recovery of PSII than short-term desiccation. This is in line with some previous studies that showed that only a prolonged stay in the desiccated state caused significant degradation of chlorophyll [41,42]. The desiccation tolerance is species-specific and depends on the speed, intensity and duration of water loss during dehydration [6].…”
Section: Discussionsupporting
confidence: 92%
“…Chlorophyll a fluorescence parameters are regarded as important tools for analyzing the functionality of photosystems under salt stress. The F v /F m is a sensitive indicator of photo-inhibition of PSII under stress ( Chowaniec and Rola, 2022 ). In K. caspia , F v /F m increased in salt treatments compared with control, indicating that salinity promoted the photosynthetic efficiency of PSII.…”
Section: Discussionmentioning
confidence: 99%
“…The photosynthetic activity of lichens is strongly related to the hydration level of their thalli. However, the amount of water in their thalli depends on climatic conditions (Chowaniec and Rola, 2022;Lange et al, 1993;ten Veldhuis, 2020). Thallus dehydration leads to a gradual loss of photosynthetic activity of the photobiont, causing changes in PS II, characterized by a decrease in the efficiency of absorbed energy transmission (Chowaniec and Rola, 2022).…”
Section: Discussionmentioning
confidence: 99%